Heterogeneity in the endocytic capacity of individual macrophage in a population determines its subsequent phagocytosis, infectivity and subcellular trafficking. (21st July 2020) - Sachdeva, Kuldeep; Goel, Manisha; Sundaramurthy, Varadharajan
Abstract: Phagocytosis is a complex cellular uptake process involving multiple distinct steps of cargo recognition, uptake, phagosome maturation and eventual phagolysosome resolution. Emerging literature shows that heterogeneity of phagocytosis at multiple steps at a single cell level influences the population outcome. However, the determinants of phagocytic heterogeneity are not clear. Here we show that the variance in the endocytic capacity of individual cells in a macrophage population determines subsequent phagocytic uptake and trafficking. Our results document the extensive heterogeneity in the endocytic uptake of individual macrophages, and show that cells with higher endocytic capacity preferentially phagocytose diverse cargo, including pathogenic Mycobacterium tuberculosis . Interestingly, M . tuberculosis infected cells sustain the higher endocytic capacity following infection. Modulating endocytic capacity by inhibiting endocytosis reduces phagocytic uptake. Differential uptake of M . tuberculosis into cells with different endocytic capacities correlates with the efficiency of phagocytic delivery to lysosomes, thus contributing further to phagocytic as well as mycobacterial heterogeneity. Thus, variance in endocytic capacity is a determinant of generating heterogeneity in phagocytosis at multiple steps. Abstract : Significant heterogeneity is observed in multiple steps of phagocytosis. While its importance in influencing population outcomes is increasingly appreciated, the determinants are unclear. Here, we show in macrophages under non‐perturbed conditions that the variance in endocytic uptake is a key determinant of phagocytic heterogeneity, including infection with Mycobacterium tuberculosis (Mtb). Further, Mtb traffics differentially to lysosomes in cells of different endocytic capacities, potentially generating intracellular Mtb diversity. Modulating the variance of endocytosis can be a means to influence multiple phagocytosis outcomes.